2003
DOI: 10.1590/s0100-29452003000300031
|View full text |Cite
|
Sign up to set email alerts
|

Development of globular embryos from the hybridization between 'Pêra Rio' sweet orange and 'Poncã' mandarin

Abstract: This research was undertaken to study the influence of different concentrations of the MT medium, sucrose, vitamins, activated charcoal and gibberellic acid (GA3) on the culture of immature embryos from the crossing between 'Pêra Rio' sweet orange and 'PONCÃ' mandarin. The embryos were excised under aseptic conditions and inoculated in 15 mL of the MT medium according to the following experiments: 1) MT concentrations (0%, 50%, 100%, 150% and 200%) supplemented with 0, 30, 60 and 90 g.L-1 of sucrose; 2) vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
6
0
2
Order By: Relevance
“…Embryos younger typically require higher concentrations of carbohydrates in the culture medium to sustain germination [43,44]. In [9] have obtained best results using 3% sucrose in the development of embryonic axes cupuaçu, in accordance with [16, 18, 19 and 45] in studies performed with Theobroma cacao.…”
Section: In Vitro Zygotic Embryo Culturesupporting
confidence: 70%
“…Embryos younger typically require higher concentrations of carbohydrates in the culture medium to sustain germination [43,44]. In [9] have obtained best results using 3% sucrose in the development of embryonic axes cupuaçu, in accordance with [16, 18, 19 and 45] in studies performed with Theobroma cacao.…”
Section: In Vitro Zygotic Embryo Culturesupporting
confidence: 70%
“…Among eight tested media, MT basal medium supplemented with 0.5 mg l À1 GA 3 was optimal for embryo culture of Satsuma mandarin, while for Red tangerine, MG1.0 medium was the best (Table 1), as with other reports (Carimi et al 1998;Yi et al 1998). However, mandarin embryos did not germinate well on MS basal medium supplemented with GA 3 (Khan et al 1996), and others reported that low concentration (0.01 mg l À1 ) of GA 3 favored the embryo germination and development of C. limonia (Ribeiro et al 2000) and sweet orange (Chagas et al 2003). The requirement for GA in embryo rescue appears to vary with species or varieties which may be due to different endogenous levels of this hormone.…”
Section: Resultsmentioning
confidence: 99%
“…Ribeiro et al (1998), estudando o cultivo in vitro de embriões de laranjeira 'Pêra' [Citrus sinensis (L.) Osbeck], observaram que a concentração de 75 % do meio de cultura de MS foi a mais responsiva para quase todas as variáveis avaliadas, indicando que os componentes da fórmula original do meio encontram-se acima do requerido para o melhor desenvolvimento e crescimento in vitro dos embriões dessa espécie. Pasqual et al (2002), estudando diferentes concentrações dos sais do MS no cultivo in vitro de embriões imaturos de tangerineira 'Poncã' (C. reticulata Blanco), observaram que o melhor resultado foi obtido com a concentração original do meio MS. Por sua vez, Chagas et al (2003a) obtiveram o melhor desenvolvimento de embriões imaturos de 'Pêra-Rio' x 'Poncã', no estádio cotiledonar, em meio de cultura contendo a concentração de 150% do meio MT, sendo que o melhor desenvolvimento desses embriões, no estádio globular, ocorreu com 50% e 100% do meio MT (Chagas et al, 2003b). Como pode ser visto, os trabalhos relacionados com a germinação de embriões imaturos utilizam reduções do meio de cultura total, ou seja, associando macronutrientes, micronutrientes e vitaminas, diferentemente do presente estudo, que testou cada conjunto de nutrientes e vitaminas separadamente.…”
Section: Ajuste De Micronutrientesunclassified
“…As variáveis comprimento de plântulas (Figura 5) e porcentagem de plântulas normais (Figura 6) apresentaram resultados ligeiramente superiores na concentração normal de vitaminas do MT (1/1), independentemente do comprimento dos embriões. Esses resultados diferem dos obtidos por Chagas et al (2003b) que, avaliando diferentes concentrações de vitaminas do meio MT no desenvolvimento de embriões globulares de citros, observaram que as vitaminas do meio de cultura MT não indicaram ser essencial para o cultivo in vitro de embriões globulares da hibridação entre 'Pêra-Rio' e 'Poncã'.…”
Section: Ajuste De Vitaminasunclassified